Juvenile fish response to wetland inundation: how antecedent conditions can inform environmental flow policies for native fish. Issue 6 (13th October 2014) - Beesley, Leah S.; Gwinn, Daniel C.; Price, Amina; King, Alison J.; Gawne, Ben; Koehn, John D.; Nielsen, Daryl L.; Crispo, Erika
Summary One of the greatest threats to lotic ecosystems is flow regulation. The impacts of flow regulation on native fish are often mitigated using periodic water allocations, termed environmental flows. The effectiveness of environmental flows has been studied in some systems, but the role of flow conditions prior to water allocation (i.e. antecedent conditions) has rarely been quantified. We evaluated the effects of floodplain inundation due to variable river flows on fish abundance in wetlands of the mid‐Murray River, Australia, using a hierarchical multi‐species model parameterized to estimate fish abundance while accounting for variable detection. We evaluated the effects of antecedent conditions on three time‐scales, including patterns in long‐term (5 years prior), medium‐term (1 year prior) and short‐term (3 months prior) wetland inundations. While species‐specific responses to antecedent conditions varied, we found a general divergence in the responses of native and non‐native species. Native fish tended to respond positively to consistent frequent inundation of wetlands, while non‐native fish tended to respond positively to long‐ or medium‐term dry periods and short‐term wet periods. Fish detection probability varied among species, sampling gears, wetland areas and wetlands, indicating that accounting for variable detection can be critical when evaluating patterns in fish abundance. Synthesis and applications. We found that antecedent conditions can be important for determining environmental water allocation policies. Our results indicated that native fish generally responded positively to frequent inundation of wetlands, while non‐native species generally responded positively to long dry periods followed by short‐term inundation events. For some non‐native species, long dry periods not only generated a positive response in abundance, but enhanced the positive response to short‐term inundation events. The divergence between native and non‐native fishes' responses to antecedent conditions provides opportunities for managers to allocate water to favour native fish assemblages. Future research of environmental flows for managing fish assemblages should consider antecedent conditions and apply models that account for incomplete detection, such as the one developed here, to better inform the management process.